Analisis Pendapatan Usahatani Kopi Arabika Di Kecamatan Marancar Kabupaten Tapanuli Selatan Provinsi Sumatera Utara - Rahmi Pohan; Farid Azel; Agustinus Mangunsong (CULTIVATE: Journal of Agriculture Science, 2025)
The aim of this research is to a) To determine the income of Arabica coffee farming in Marancar District, South Tapanuli Regency, North Sumatra Province. b) To find out whether the average income for Arabica coffee in Marancar District, South Tapanuli Regency, North Sumatra Province is greater or less than the UMP value for North Sumatra Province. c) To determine the financial feasibility of arabica coffee farming in Marancar District, South Tapanuli Regency, North Sumatra Province. The time for conducting the research is from April-June 2024. The sampling method uses the Purposive Sampling method with a sample size of 40 Arabica coffee farmers. The data analysis method used is the Z Test comparison and farming analysis (income, R/C ratio, BEP). The research results show that the average monthly income of Arabica coffee farmers is IDR 2,273,161. Comparison of the Z test, the income of Arabica coffee farmers is smaller than the North Sumatra Province Minimum Wage of IDR 2,809,925/month with the farming feasibility level, namely the R/C ratio value of 1.9, which is said to be feasible to cultivate because the value is 1. The revenue BEP is IDR 684,990, the production BEP is 35 kg, and the price BEP is IDR 36,307.